Note subjective sur le style flaubertien - Philippe Jousset (Flaubert: Revue Critique et Génétique)
A letter to the doctor Jules Cloquet, written in Cairo, is chosen as a sample of Flaubert’s correspondence in the 1850’s. Representative of what is called the “average” epistolary writing, it can be used as a negative to understand to what extent the novelist engaged in self-mutilation so as to “faire oeuvre” by perfecting the art of prose that has brought him so much praise. The major issues is that by becoming a totem Flaubert’s style has given literature and its teaching in France a decisive orientation, of which today’s debates show the historicity.